2016
DOI: 10.1073/pnas.1601569113
|View full text |Cite
|
Sign up to set email alerts
|

FOXC1 maintains the hair follicle stem cell niche and governs stem cell quiescence to preserve long-term tissue-regenerating potential

Abstract: Adult tissue stem cells (SCs) reside in niches, which orchestrate SC behavior. SCs are typically used sparingly and exist in quiescence unless activated for tissue growth. Whether parsimonious SC use is essential to conserve long-term tissue-regenerating potential during normal homeostasis remains poorly understood. Here, we examine this issue by conditionally ablating a key transcription factor Forkhead box C1 (FOXC1) expressed in hair follicle SCs (HFSCs). FOXC1-deficient HFSCs spend less time in quiescence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 46 publications
4
119
2
Order By: Relevance
“…As shown in Fig 1A, the mRNA of FOXC1 was significantly up-regulated during the course of KC differentiation, and its protein expression was also gradually increased in differentiated KC (Fig 1B). A recent paper reported that FOXC1 is expressed in mouse hair follicles but absent in mouse epidermis [11]. In our study, however, we find that FOXC1 is expressed not only in human hair follicles, but also in the differentiated KC of inner hair root sheath that surrounds the hair shaft and the epidermis upper layers of KC (Fig 1C).…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…As shown in Fig 1A, the mRNA of FOXC1 was significantly up-regulated during the course of KC differentiation, and its protein expression was also gradually increased in differentiated KC (Fig 1B). A recent paper reported that FOXC1 is expressed in mouse hair follicles but absent in mouse epidermis [11]. In our study, however, we find that FOXC1 is expressed not only in human hair follicles, but also in the differentiated KC of inner hair root sheath that surrounds the hair shaft and the epidermis upper layers of KC (Fig 1C).…”
Section: Resultscontrasting
confidence: 55%
“…Recently, while we were revising our submission, Cui et al published elegant work on the Journal of Investigative Dermatology reporting that specifically disrupted FOXC1 gene expression in mouse sweat gland epithelium led to symptoms of hypohidrosis; loss of FOXC1 in mouse sweat gland epithelium led to enhanced gene expression of Sprr2a/b and KRT8 which formed a plug to block sweat gland secretion ducts[26]. However, similar to Lay et al’ s report[11], this article by Cui et al did not show FOXC1 gene expression in mouse epidermis. Comparing our data generated from human primary KC and human skin biopsies with data from Lay et al and Cui et al using murine models, we think FOXC1 may function differently in human epidermis from mouse epidermis.…”
Section: Discussionmentioning
confidence: 81%
“…Foxc1 also controls vascular growth in the cornea and outgrowth and branching of lacrimal glands (Mattiske et al, 2006; Seo et al, 2012). Extraocular features have also been reported in Foxc1 mutant patients (Kume, 2009), and two recent studies published during submission of this manuscript showed that Foxc1 regulates hair follicle stem cell quiescence (Lay et al, 2016; Wang et al, 2016). We had earlier noted that Foxc1 was highly expressed in mouse sweat glands (Kunisada et al, 2009), but no corresponding function had been determined.…”
Section: Resultsmentioning
confidence: 61%
“…Foxc1 was shown to be a transcriptional activator in most published cases (Lay et al, 2016; Wang et al, 2016), and thus our finding of repressive action on sweat duct luminal cell differentiation implied a surprisingly different mechanism. Therefore, we further analyzed whether Foxc1 represses those differentiation markers in a keratinocyte culture system.…”
Section: Discussionmentioning
confidence: 69%
“…The new hair shaft will begin to emerge once the telogen phase is complete. The process results in normal hair loss known as shedding (Lay et al 2016). Under normal depilation treatment, hair will enter the growing period and appear be a lot of new nipple.…”
Section: -Gingerol Inhibits Hair Cycle 2715mentioning
confidence: 99%